2018
DOI: 10.1523/jneurosci.2821-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Balance between Striatal Feedforward Inhibition and Corticostriatal Excitation Leads to Tremor

Abstract: Fast-spiking interneurons (FSIs) exert powerful inhibitory control over the striatum and are hypothesized to balance the massive excitatory cortical and thalamic input to this structure. We recorded neuronal activity in the dorsolateral striatum and globus pallidus (GP) concurrently with the detailed movement kinematics of freely behaving female rats before and after selective inhibition of FSI activity using IEM-1460 microinjections. The inhibition led to the appearance of episodic rest tremor in the body par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…2 Similarly, animal studies have shown that reduced putaminal feedforward inhibition produces paroxysmal dystonia in the dt sz mutant hamster, 37 while selective inhibition of fast-spiking interneurons in rodents leads to dyskinesia, dystonia, and episodic tremor. 38,39 The manifested symptom variability was attributed to the differences between species and experimental and analytic protocols. Based on its symptomatology, frequency, and harmonics, an argument was made that selective inhibition of feedforward projections from fast-spiking interneurons leads to tremor rather than other types of movement disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Similarly, animal studies have shown that reduced putaminal feedforward inhibition produces paroxysmal dystonia in the dt sz mutant hamster, 37 while selective inhibition of fast-spiking interneurons in rodents leads to dyskinesia, dystonia, and episodic tremor. 38,39 The manifested symptom variability was attributed to the differences between species and experimental and analytic protocols. Based on its symptomatology, frequency, and harmonics, an argument was made that selective inhibition of feedforward projections from fast-spiking interneurons leads to tremor rather than other types of movement disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Based on its symptomatology, frequency, and harmonics, an argument was made that selective inhibition of feedforward projections from fast-spiking interneurons leads to tremor rather than other types of movement disorders. 39 Characteristic to tremor, abnormal firing patterns of putaminal and pallidal neurons were temporarily and spatially correlated, becoming oscillatory and coherent with large-amplitude tremor. 39 Notably, selective reduction of the excitatory corticostriatal input resulted in the disappearance of tremor and the reversal of temporal and spatial correlatory activity.…”
Section: Discussionmentioning
confidence: 99%
“…choice execution) but not others (cue or reward). The causal role of FSI was first probed by pharmacological blockade: striatal local infusion of IEM-1460, which silences the FSI population, causes dyskinesia and tremor in mice (Gittis et al 2011;Oran and Bar-Gad 2018), consistent with the role of FSI in tuning SPN activity and suppressing undesired movements. In more recent years, use of genetic tools has allowed selective, bidirectional manipulation of FSI activity to see the consequence on behavioral tasks.…”
Section: Fsis Are Key Determinants Of Pathophysiology In Movement Dismentioning
confidence: 93%
“…In four animals, additional recording electrodes were placed in the dorsolateral striatum (AP: 0.5, ML: 4.0, DV: 3.5-5.5). All the surgical procedures were described in detail in previous studies by our group (Bronfeld et al, 2013;Yael et al, 2013;Israelashvili and Bar-Gad, 2015;Oran and Bar-Gad, 2018).…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…In this study we use disinhibition to deconstruct the behavioral elements controlled by the NAc core on multiple timescales and identify the underlying neurophysiological mechanism encoding these elements. The relation between behavior and striatal activity has been explored during in the dorsolateral striatum during normal behavior (Klaus et al, 2017;Markowitz et al, 2018) and disinhibition (Bronfeld et al, 2011;Israelashvili and Bar-Gad, 2015;Oran and Bar-Gad, 2018) but is lacking for the ventral striatum during either states. This neuronal-behavioral relationship may serve as a basis for establishing the unique role of the NAc in the control of movement in normal and hyperkinetic conditions.…”
Section: Introductionmentioning
confidence: 99%